(untitled) (Research, Society and Development, 2021)
To evaluate the protective effect of rhinoplasty with diode laser on the cardiovascular system and in the reduction of the inflammatory state, CK-MB and PCR measurements were performed before and 30 days after the surgical procedure. Rhinoplasty using the diode laser promoted a significant reduction in plasma CK-MB and PCR levels, 30 days after its completion. No association was found between the pre-surgical plasma concentration of CK-MB and CRP and the degree of stenosis of the nostrils, race, age, sex and weight of the animals. A significant reduction in CK-MB was observed in dogs with severe stenosis, French Bulldog, one year old and over four years old, male and between 10 and 20 kg. Animals with severe stenosis, of the Pug breed, weighing less than 10 kg and three years of age exhibited a significant decrease in serum CRP values ​​after surgery. As a result, the degree of stenosis of the nostrils, the breed, age, sex and weight of the animals did not influence the plasma concentration of NTpro-BNP, CK-MB and PCR in brachycephalic dogs. Rhinoplasty with diode laser has been shown to be effective in reducing the plasma concentration of the natriuretic peptide CK-MB and CRP in dogs with brachycephalic syndrome, showing that the procedure has a protective effect on the cardiovascular function of these animals and is also effective in reducing inflammatory biomarkers.